Factors affecting behaviour of Income Zakat payment among FELDA settlers during COVID-19 Pandemic - Hairunnizam Wahid; Anida Norlena Salim; Mohamad Syahmi Mat Daud; Mohd Adib Ismail (International Journal of Zakat, 2022)
As a Muslim who believes in Allah SWT, the responsibility to give zakat is one of the beliefs that must be implemented. And a Muslim should spend part of the property sincerely because Allah pleases alms. Internal and external factors that occur around an individual will affect his thoughts and behavior. Since the declaration of the COVID-19 pandemic announced by the World Health Organization (WHO), the whole world has been at war with the pandemic phenomenon of coronavirus outbreak. During that period, the world seemed to experience a "reset" in terms of economic and social aspects in the activities of individuals as an individual or a group. In this situation, imbalances in the socio-economy of society occur at all levels of the rich and the poor. At this point, zakat is one of the solutions to fix this imbalance. Various efforts have been moved by zakat institutions to increase awareness and attract the interest of the local Muslim community to issue income zakat on a regular basis. However, there is no special legal provision on the obligation to pay zakat, but voluntary obedience as a servant to the Almighty Creator is the inner strength. Therefore, this research was conducted through a survey of 552 respondents of the Settlers in FELDA Johor Baharu Region aiming to study the factors that affect the awareness of the Muslim community living in the settlement which has a planned social and spiritual program. This study employed quantitative methods through the distribution of questionnaires in form of binary questions and Likert scales. Descriptive statistical analysis was also used to look at the relationship of the factors influencing the behavior of respondents to issue income zakat during the COVID-19 pandemic. The results of the study found that the dependent factor which was the intention was the only significant factor on the behavior of FELDA Settlers to issue income zakat post-pandemic COVID-19. Other independent factors were not significant but there was still a positive relationship to the behavior of zakat payment among the Settlers in the Johor Bahru Region. The results of the study found that factors of age, religious influences, and courtesy were the driving forces behind the Settlers' awareness. Keywords: Religion, FELDA, behavior, compliance, awareness, income Zakat, COVID-19 pandemic time